Role of CCRT In T3n0 Squamous Cell Carcinoma Larynx, Pros Vs Cons - Khan, Ayesha; Naeem Riaz; Faisal Manzoor; Kamran Zamurrad Malik; Shakeel Ahmed; Muhammad Ali (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the use and efficacy of Concurrent Chemoradiotherapy for a T3N0 Laryngeal Cancer as a Laryngeal Function Preservation modality. Study Design: Prospective Study design Place and Duration of Study: CMH Rawalpindi, Pakistan from January 2022-January 2023. Methodology: The sample size was n=24, having TPF-CCRT from January 2022 to January 2023 was chosen by using a purposive sampling technique. Individuals were having abnormalities of T3 glottis without vocal cord fixation. Along with MRI, the pretreatment evaluation also comprised clinical, endoscopy, and ultrasound examinations with or without fine needle pick cytology samples. Moreover, F-fluoro-2-deoxy-D-glucose positron emitting tomography was used for whole-body CT scanning. The UICC TNM grading method was used to grade the tumors as grade 15. Results: Twelve out of 24 patients had grade 1 tumor (50%), eight had grade 2 tumors (25%), and four had grade 3 tumors (25%). There had been complete resolution among 17 (70%) of patients, while the disease remains persistent disease in 7 (30%) patients. 95% of patients found with good speech and breathing. 95% of patient organs remain preserved. All 24 patients received CCRT. Four individuals (20%) without tumor regression received surgery following 40 Gy of RT. Others received RT with a 66 Gy median total dose. Conclusion: The study found that effective cancer control is possible with CCRT, and its effects are manageable in 70% of patients with tolerable toxicity. However, in 30% of cases, it fails, requiring salvage laryngectomy. However, the search for a viable strategy with tolerabl